A stainless steel material for food-grade straws and its preparation process

By performing electroless silver plating and plasma silver penetration treatment on the surface of stainless steel pipes, combined with antibacterial coatings, the wear resistance and antibacterial properties of food-grade stainless steel materials are solved, the hardness and antibacterial properties of the material are improved, and the service life is extended.

CN120425423BActive Publication Date: 2025-09-02JIANGSU YONGJIN METAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510933302.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2025-09-02
Estimated Expiration
2045-07-08

AI Technical Summary

Technical Problem

The existing food-grade stainless steel materials are not wear-resistant during use and lack antibacterial ability, which leads to scratches on the surface and reduces corrosion resistance.

Method used

By electroless silver plating and plasma silver filtration treatment on the surface of stainless steel pipes, a silver plating layer and silver filtration layer are formed and an antibacterial coating is applied thereto, and the hardness and antibacterial properties of the material are improved by synergistic action of sulfonic acid groups and nano silver.

Benefits of technology

It achieves high hardness, antibacterial and wear resistance of stainless steel materials, extends service life, and improves antibacterial performance and weather resistance through double-layer protective layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention discloses a stainless steel material for food-grade straws and a preparation process thereof, and relates to the technical field of stainless steel plating. The present invention provides a silver-plated layer and an antibacterial coating on the surface of the stainless steel material. Through the action of the double protective layer, the stainless steel material has both good wear resistance and antibacterial properties. The present invention adds sulfonated polyphenylene sulfide to the silver plating solution and forms a coating after electroplating, which can make the surface of the stainless steel material less prone to scratches and improve the wear resistance of the stainless steel. In addition, by adding quaternary ammonium salt-modified tea polyphenol-nanosilver composite particles to the antibacterial coating, the synergistic antibacterial action of the quaternary ammonium salt, tea polyphenol and nanosilver is achieved to achieve broad-spectrum antibacterial properties and achieve a highly effective antibacterial effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of stainless steel surface plating, in particular to a stainless steel material for food-grade straws and a preparation process thereof. Background Art

[0002] Food-grade stainless steel refers to stainless steel materials that comply with the "National Standard of the People's Republic of China / Hygiene Standard for Stainless Steel Tableware Containers" GB4806.9-2016. This material will not dissolve alloys and harmful substances when used. The food-grade stainless steel materials currently used on the market can be divided into three grades: 430, 304 (18-8) and 18-10. Depending on the raw materials, the corrosion resistance of the resulting stainless steel is also different. These three grades correspond to high-end, mid-range and low-end tableware respectively.

[0003] However, the tableware currently on the market has common shortcomings: insufficient wear resistance and no antibacterial ability; after a period of use, scratches will appear on the surface of the material, which is unsightly and reduces corrosion resistance; with the increasing demand for public health and quality of life, the safety of tableware has gradually been paid attention to. Stainless steel materials can be seen everywhere in household kitchen utensils, and the demand for antibacterial tableware is increasing.

[0004] Therefore, we propose a stainless steel material for food-grade straws and a preparation process thereof, so that the stainless steel material has higher hardness and better antibacterial properties. Summary of the Invention

[0005] The object of the present invention is to provide a food-grade stainless steel material for straws and a preparation process thereof, so as to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solution: a process for preparing stainless steel material for food-grade straws, comprising the following steps:

[0007] Take the stainless steel tube, place it in the silver plating solution for chemical silver plating to form a silver plating layer, and then evacuate to 4×10 -3 Pa, plasma silvering treatment is performed to form a silver-infiltrated layer to obtain a stainless steel material for food-grade straws.

[0008] Furthermore, the stainless steel tube is food grade 304 stainless steel or food grade 316 stainless steel.

[0009] Furthermore, the process conditions of the silver plating are: bath temperature 20°C~40°C, electroplating time 15min~25min, current density 2A / dm 2 ~4A / dm 2 .

[0010] Furthermore, the gas used in the plasma silvering treatment is argon;

[0011] The process conditions of the plasma silvering treatment are: temperature 600° C. to 700° C., voltage 1.1 kV to 1.3 kV, current 3 A to 5 A, time 2 h to 4 h, and argon flow rate 30 mL / min to 50 mL / min.

[0012] Furthermore, the silver plating solution is prepared by the following process:

[0013] Take silver nitrate, stir and dissolve it in deionized water, add ammonia water until a black flocculent precipitate is formed and then dissolve it again to obtain a silver ammonia solution, then add glucose, sulfonated polyphenylene sulfide, 5,5-dimethylhydantoin and polyethylene glycol sulfonate, adjust the pH to 11-13, and obtain a silver plating solution.

[0014] Furthermore, the silver plating solution includes the following components by mass: 15g / L~20g / L silver nitrate, 20g / L~30g / L sulfonated polyphenylene sulfide, 10g / L~20g / L glucose, 40g / L~60g / L 5,5-dimethylhydantoin, 0.1g / L~0.5g / L polyethylene glycol sulfonate, and 0.12mL~0.14mL ammonia water;

[0015] The solvent of the silver plating solution is deionized water.

[0016] Furthermore, the concentration of the ammonia water is 3 mol / L.

[0017] Furthermore, the sulfonated polyphenylene sulfide is prepared by the following process:

[0018] S1: mixing polyphenylene sulfide and dopamine solution, stirring for 0.5 h to 1.5 h, and adjusting the pH to 8.0 to 9.0 to obtain polydopamine-modified polyphenylene sulfide;

[0019] S2: taurine is mixed with deionized water to obtain a mixed solution; polydopamine-modified polyphenylene sulfide is mixed with the mixed solution, and under the protection of a nitrogen atmosphere, the pH is adjusted to 7-9, the reaction is stirred, and the mixture is dried to obtain sulfonated polyphenylene sulfide.

[0020] Furthermore, in S1, the dopamine solution is a mixture of dopamine hydrochloride and Tris-HCl buffer;

[0021] The mass ratio of dopamine hydrochloride to Tris-HCl buffer is (0.08-0.12):10;

[0022] The concentration of the Tris-HCl buffer is 0.4 mol / L.

[0023] Furthermore, in S1, the mass ratio of the polyphenylene sulfide to the dopamine solution is 1:(15-25).

[0024] Furthermore, in S2, the mass ratio of taurine to deionized water is 1:(3-5);

[0025] In S2, the mass ratio of the polydopamine-modified polyphenylene sulfide to the mixed solution is 1:(1-5).

[0026] In the above technical solution, polyphenylene sulfide is coated with polydopamine, and sulfonic acid groups are then grafted onto the surface of the polydopamine, so that the surface of the polyphenylene sulfide has sulfonic acid groups. When added to the silver plating solution, the sulfonic acid groups have good adsorption capacity with silver ions, which can promote the deposition and embedding of silver ions. After electroplating, the formed silver plating layer is uniform and dense. The sulfonic acid groups can also slow the reduction rate of silver ions, improve the gloss of the plating layer, and enhance the aesthetics of the straw.

[0027] In the silver plating solution, 5,5-dimethylhydantoin acts as a stabilizer to promote the formation of fine and uniform grains in the silver plating layer, thereby improving the gloss and hardness of the coating. Polyethylene glycol sulfonate has dispersing and wetting effects, and the strong hydrophilicity of the sulfonic acid group enables it to be evenly dispersed in the silver plating solution, reducing surface tension and reducing defects such as pinholes and pitting on the surface of the coating.

[0028] Furthermore, the surface of the silver-infiltrated layer is provided with an antibacterial coating, which is formed by coating and drying an antibacterial coating;

[0029] The antibacterial coating is prepared by the following process:

[0030] The quaternary ammonium salt modified tea polyphenol-nanosilver composite particles, a curing agent, a solvent and a leveling agent are mixed and stirred evenly to obtain an antibacterial coating.

[0031] Furthermore, the mass ratio of the quaternary ammonium salt modified tea polyphenol-nanosilver composite particles, curing agent, solvent, and leveling agent is 1: (0.01-0.05): (5-15): (0.03-0.05).

[0032] Furthermore, the curing agent is one of dibenzoyl peroxide, hexahydrophthalic anhydride, and methyltetrahydrophthalic anhydride;

[0033] The solvent is a mixture of one or more of ethyl acetate, butyl acetate, isopropyl alcohol, and hexamethyldisiloxane;

[0034] The leveling agent is polydimethylsiloxane.

[0035] Furthermore, the quaternary ammonium salt-modified tea polyphenol-nanosilver composite particles are prepared by the following process:

[0036] S1: adding tea polyphenols to a reactor, passing liquid ammonia, reacting at low temperature, and drying to obtain amino tea polyphenols; mixing amino tea polyphenols, deionized water, and long-chain quaternary ammonium salt, heating in a water bath for reaction, standing for 18 h to 22 h, and drying to obtain quaternary ammonium salt-modified tea polyphenols;

[0037] S2: TiO2 (titanium dioxide) was mixed with deionized water and ultrasonically dispersed. EDC solution (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide) amine and PAA solution (polyacrylic acid) were added. The mixture was ultrasonically stirred in an ice bath and washed to obtain modified TiO2.

[0038] S3: Mixing the modified TiO2, quaternary ammonium salt-modified tea polyphenols, and deionized water, stirring and reacting, washing, and obtaining an assembled product, mixing the assembled product with deionized water and a 0.5 mg / mL trisodium citrate aqueous solution, stirring and reacting, washing, and drying to obtain quaternary ammonium salt-modified tea polyphenol-TiO2 composite particles;

[0039] S4: Mix the modified tea polyphenol-TiO2 composite particles, deionized water and AgNO3 aqueous solution, boil them, and keep them for 0.5h~1h, wash and dry them to obtain quaternary ammonium salt modified tea polyphenol-nanosilver composite particles.

[0040] Furthermore, in S1, the tea polyphenol is green tea extract, and the tea polyphenol is added in the form of powder with a mesh size of 80 mesh;

[0041] The long-chain quaternary ammonium salt is one of dodecyltrimethylammonium bromide and hexadecyltrimethylammonium bromide.

[0042] Furthermore, in S1, the molar ratio of liquid ammonia to phenolic hydroxyl groups in tea polyphenols is (3-5):1;

[0043] The ratio of amino tea polyphenols, deionized water and long-chain quaternary ammonium salt is 10g: (0.05~0.1)L: (40~60)g.

[0044] Furthermore, in S1, the process conditions of the low-temperature reaction are: temperature -15°C to -25°C, pressure 0.1MPa to 0.8MPa, and time 16h to 24h;

[0045] In S1, the process conditions of the water bath heating reaction are: temperature 60°C to 80°C, time 1h to 3h.

[0046] Furthermore, in S2, the ratio of TiO2, deionized water, EDC solution and PAA solution is 10 mg: (10-50) mL: (0.05-0.1) mL: (0.25-0.45) mL.

[0047] Furthermore, in S2, the TiO2 is added in the form of powder with a particle size of 5nm~10nm;

[0048] In S2, the concentration of the EDC solution is 0.025 g / mL;

[0049] The concentration of the PAA solution is 40 mg / mL.

[0050] Furthermore, in S2, the process conditions of ultrasonic dispersion are: frequency 50kHz~100kHz, time 5min~15min;

[0051] In S2, the process conditions of ice bath ultrasonic stirring are: frequency 50 kHz~100 kHz, time 25 min~35 min, and stirring speed 100 rpm~200 rpm.

[0052] Furthermore, in S3, the ratio of the modified TiO2, quaternary ammonium salt-modified tea polyphenols, and deionized water is 1 mg: (1-3) mL: (5-15) mL;

[0053] The ratio of the assembled product, deionized water, and trisodium citrate aqueous solution is 1 mg: (3-5) mL: (3-8) mL.

[0054] Furthermore, in S3, the process conditions of the stirring reaction are: rotation speed 300 rpm~500 rpm, time 20 min~40 min.

[0055] Furthermore, S3 needs to be repeated 3 to 5 times.

[0056] Furthermore, in S4, the ratio of the modified tea polyphenol-TiO2 composite particles, deionized water and AgNO3 aqueous solution is 1 g: (50-100) mL: (100-200) mL.

[0057] Furthermore, in S4, the concentration of the AgNO3 aqueous solution is 1 mg / mL.

[0058] In the above technical solution, tea polyphenols are first quaternized to graft long-chain quaternary ammonium salts onto the tea polyphenols, and then PAA is modified on the TiO2 surface, which can reduce the agglomeration phenomenon between TiO2 nanoparticles and also make TiO2 have a negative charge, so that the tea polyphenols with quaternary ammonium salts are assembled onto the TiO2 surface through electrostatic adsorption, thereby preparing modified tea polyphenol-TiO2 composite particles. Finally, under boiling conditions, silver ions in silver nitrate are reduced to zero-valent silver to form nanosilver particles, which are assembled onto the TiO2 surface through electrostatic adsorption. No additional reducing agent is required, the operation is simple, and the process has good economic benefits.

[0059] Tea polyphenols can bind to enzymes in bacteria, blocking DNA replication and protein synthesis, and can also scavenge free radicals produced by bacterial metabolism, thereby achieving an antibacterial effect; the positive charge of quaternary ammonium salts combines with the negative charge of bacterial cell membranes, disrupting the membrane arrangement, increasing membrane permeability, allowing substances inside the membrane to leak out, and inhibiting bacterial growth; nanosilver can directly penetrate the cell membrane to achieve an antibacterial effect; the three antibacterial substances work synergistically to achieve broad-spectrum antibacterial properties and achieve high antibacterial efficiency;

[0060] Nano-TiO2 has the advantages of small size and large specific surface area. It can fully adsorb antibacterial components, provide more targets for contact with bacteria, and improve antibacterial ability. At the same time, TiO2 has good high temperature resistance and weather resistance, and is highly safe. Using it as a coating can make the formed coating have good wear resistance, less prone to scratches, and extend the service life of the base material.

[0061] Compared with the prior art, the present invention has the following beneficial effects:

[0062] 1. Polyphenylene sulfide itself has good corrosion resistance, weather resistance and wear resistance. When added to the plating solution and electroplated to form a coating, it can make the surface of stainless steel less likely to be scratched, improve the corrosion resistance of stainless steel, and extend its service life;

[0063] The present invention coats polydopamine on the surface of polyphenylene sulfide and then grafts sulfonic acid groups on the surface of the polydopamine, so that the surface of the polyphenylene sulfide has sulfonic acid groups. When the polyphenylene sulfide is added to a silver plating solution, the sulfonic acid groups have good adsorption capacity with silver ions, which can promote the deposition and embedding of silver ions. After electroplating, the formed silver plating layer is uniform and dense. The sulfonic acid groups can also slow down the reduction rate of silver ions, improve the glossiness of the plating layer, and enhance the aesthetics of the straw.

[0064] In the silver plating solution, 5,5-dimethylhydantoin acts as a stabilizer to promote the formation of fine and uniform grains in the silver plating layer, thereby improving the gloss and hardness of the coating. Polyethylene glycol sulfonate has dispersing and wetting effects, and the strong hydrophilicity of the sulfonic acid group enables it to be evenly dispersed in the silver plating solution, reducing surface tension and reducing defects such as pinholes and pitting on the surface of the coating.

[0065] 2. By quaternizing tea polyphenols, grafting long-chain quaternary ammonium salts onto tea polyphenols, and then modifying the TiO2 surface with PAA, the agglomeration of TiO2 nanoparticles can be reduced, and TiO2 can also be negatively charged, so that the tea polyphenols with quaternary ammonium salts can be assembled onto the TiO2 surface through electrostatic adsorption, thereby preparing modified tea polyphenol-TiO2 composite particles. Finally, under boiling conditions, the silver ions in the silver nitrate are reduced to zero-valent silver to form nanoparticles, which are assembled onto the TiO2 surface through electrostatic adsorption. No additional reducing agent is required, the operation is simple, and it has good economic benefits.

[0066] Tea polyphenols can bind to enzymes in bacteria, blocking DNA replication and protein synthesis, and can also scavenge free radicals produced by bacterial metabolism, thereby achieving an antibacterial effect; the positive charge of quaternary ammonium salts combines with the negative charge of bacterial cell membranes, disrupting the membrane arrangement, increasing membrane permeability, allowing substances inside the membrane to leak out, and inhibiting bacterial growth; nanosilver can directly penetrate the cell membrane to achieve an antibacterial effect; the three antibacterial substances work synergistically to achieve broad-spectrum antibacterial properties and achieve high antibacterial efficiency;

[0067] Nano-TiO2 has the advantages of small size and large specific surface area. It can fully adsorb antibacterial components, provide more targets for contact with bacteria, and improve antibacterial ability. At the same time, TiO2 has good high temperature resistance and weather resistance, and is highly safe. Using it as a coating can make the formed coating have good wear resistance, less prone to scratches, and extend the service life of the base material.

[0068] 3. After silver plating, plasma silver diffusion treatment is carried out to deposit silver ions into the lattice on the surface of the stainless steel, avoiding microporous defects caused by impurities during silver plating. At the same time, long-term antibacterial effect is achieved by slowly releasing silver ions.

[0069] 4. The antibacterial coating contains quaternary ammonium ions, which can improve the bonding strength between the silver plating layer and the antibacterial coating through electrostatic adsorption with the sulfonic acid groups in the silver plating layer; through the action of the double protective layer, internal and surface antibacterial properties are achieved at the same time, greatly improving the antibacterial properties of the stainless steel straws, and also improving the wear resistance and weather resistance of the stainless steel straws. DETAILED DESCRIPTION

[0070] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0071] In the following specific embodiments,

[0072] The stainless steel tube is food-grade 316 stainless steel, with a diameter of 1.5 mm and a thickness of 0.015 mm, and is manufactured in accordance with GB 4806.9-2023. It is sourced from Jiangsu Yongjin Metal Technology Co., Ltd.

[0073] The polyphenylene sulfide is food grade polyphenylene sulfide with a particle size of 0.1 μm and an average molecular weight of 30,000 g / mol;

[0074] The curing agent is methyltetrahydrophthalic anhydride;

[0075] The solvent is hexamethyldisiloxane;

[0076] The leveling agent is polydimethylsiloxane;

[0077] Tea polyphenols powder, mesh size 80 mesh;

[0078] The long-chain quaternary ammonium salt is cetyltrimethylammonium bromide;

[0079] TiO2 powder, particle size 5nm;

[0080] EDC solution, concentration 0.025 g / mL;

[0081] PAA solution, concentration 40 mg / mL, average molecular weight 5000 Mw;

[0082] AgNO3 aqueous solution, concentration 1 mg / mL;

[0083] trisodium citrate aqueous solution, concentration 0.5 mg / mL;

[0084] Ammonia water, concentration 3 mol / L;

[0085] Tris-HCl buffer, concentration 0.4 mol / L;

[0086] Glucose solution, concentration is 20g / L.

[0087] Example 1: A process for preparing a food-grade stainless steel straw, comprising the following steps:

[0088] (1) Preparation of antibacterial coating:

[0089] S1: Add tea polyphenols into a reactor, pass liquid ammonia, react at low temperature, and dry to obtain amino tea polyphenols; mix amino tea polyphenols, deionized water and hexadecyltrimethylammonium bromide at a ratio of 10g:0.05L:60g, heat in a water bath at 80℃ for 3h, let stand for 22h, and dry to obtain quaternary ammonium salt modified tea polyphenols; the process conditions for low temperature reaction are: temperature -25℃, pressure 0.8MPa, time 24h; the molar ratio of liquid ammonia to phenolic hydroxyl groups in tea polyphenols is 5:1; S2: Take TiO2, mix it with deionized water, ultrasonically disperse it at 100kHz for 15min, add EDC solution and PAA solution, ultrasonically stir it in an ice bath, and wash to obtain modified TiO2; the ratio of TiO2, deionized water, EDC solution and PAA solution is 10mg:10mL:0.1mL:0.45mL; the process conditions for ultrasonic stirring in an ice bath are: : frequency 100kHz, time 35min, stirring speed 200rpm; S3: modified TiO2, quaternary ammonium salt modified tea polyphenols, and deionized water are mixed in a ratio of 1mg:3mL:5mL, stirred for reaction, washed to obtain an assembled product, which is mixed with deionized water and trisodium citrate aqueous solution, stirred for reaction, washed, and dried to obtain quaternary ammonium salt modified tea polyphenol-TiO2 composite particles; the ratio of the assembled product, deionized water, and trisodium citrate aqueous solution is 1mg:3mL:8mL; the process conditions for the stirring reaction are: speed 500rpm, time 40min; the operation is repeated 5 times; S4: modified tea polyphenol-TiO2 composite particles, deionized water, and AgNO3 aqueous solution are mixed in a ratio of 1g:50mL:100mL, boiled, and kept for 1h, washed, and dried to obtain quaternary ammonium salt modified tea polyphenol-nanosilver composite particles;

[0090] The quaternary ammonium salt-modified tea polyphenol-nanosilver composite particles, methyltetrahydrophthalic anhydride, hexamethyldisiloxane, and polydimethylsiloxane are mixed in a mass ratio of 1:0.05:15:0.05, and stirred evenly to obtain an antibacterial coating;

[0091] (2) Preparation of silver plating solution:

[0092] Dopamine hydrochloride and Tris-HCl buffer were mixed at a mass ratio of 0.12:10 to obtain a dopamine solution;

[0093] S1: polyphenylene sulfide and dopamine solution were mixed in a mass ratio of 1:25, stirred for 1.5 hours, and the pH was adjusted to 9.0 to obtain polydopamine-modified polyphenylene sulfide; S2: taurine and deionized water were mixed in a mass ratio of 1:3 to obtain a mixed solution; polydopamine-modified polyphenylene sulfide was mixed with the mixed solution in a mass ratio of 1:5, and under nitrogen atmosphere, the pH was adjusted to 9, stirred for reaction, and dried to obtain sulfonated polyphenylene sulfide;

[0094] Silver nitrate was dissolved in deionized water with stirring, and ammonia was added until a black flocculent precipitate was formed and then dissolved again to obtain a silver ammonia solution. Glucose, sulfonated polyphenylene sulfide, 5,5-dimethylhydantoin and polyethylene glycol sulfonate were then added and the pH was adjusted to 13 to obtain a silver plating solution.

[0095] The silver plating solution includes the following components by mass: 20 g / L silver nitrate, 30 g / L sulfonated polyphenylene sulfide, 20 g / L glucose, 60 g / L 5,5-dimethylhydantoin, 0.5 g / L polyethylene glycol sulfonate, and 0.14 mL ammonia water;

[0096] (3) Preparation of stainless steel materials for food-grade straws:

[0097] Take a food grade 316 stainless steel tube, perform plasma treatment, place it in a silver plating solution for chemical silver plating to form a silver plating layer, and then evacuate to 4×10 -3 Pa, argon gas is passed through, plasma silvering treatment is performed to form a silver-infiltrated layer, antibacterial coating is applied, and drying is performed to form an antibacterial coating to obtain a stainless steel material for food-grade straws; plasma treatment uses a mixed gas of argon and oxygen, and the volume ratio of argon to oxygen is 1:6.5; the process conditions of plasma treatment are: mixed gas flow rate 250sccm, processing power 160W, and processing time 3min; the process conditions of silver plating are: plating solution temperature 40℃, electroplating time 25min, current density 4A / dm 2 The process conditions of plasma silvering treatment are: temperature 700℃, voltage 1.3kV, current 5A, time 4h, argon flow rate 50mL / min.

[0098] Example 2: A process for preparing a food-grade stainless steel straw, comprising the following steps:

[0099] (1) Preparation of antibacterial coating:

[0100] S1: Add tea polyphenols into a reactor, pass liquid ammonia, react at low temperature, and dry to obtain amino tea polyphenols; mix amino tea polyphenols, deionized water and cetyltrimethylammonium bromide at a ratio of 10g:0.08L:50g, heat in a water bath at 70°C for 2h, let stand for 20h, and dry to obtain quaternary ammonium salt modified tea polyphenols; the process conditions for low-temperature reaction are: temperature -20°C, pressure 0.5MPa, time 20h; the molar ratio of liquid ammonia to phenolic hydroxyl groups in tea polyphenols is 4:1; S2: Take TiO2, mix it with deionized water, ultrasonically disperse it at 80kHz for 10min, add EDC solution and PAA solution, ultrasonically stir it in an ice bath, and wash it to obtain modified TiO2; the ratio of TiO2, deionized water, EDC solution and PAA solution is 10mg:30mL:0.08mL:0.35mL; the process conditions for ultrasonic stirring in an ice bath are: Frequency 80kHz, time 30min, stirring speed 150rpm; S3: Modified TiO2, quaternary ammonium salt modified tea polyphenols, and deionized water are mixed in a ratio of 1mg:2mL:10mL, stirred for reaction, washed to obtain an assembled product, mixed with deionized water and trisodium citrate aqueous solution, stirred for reaction, washed, and dried to obtain quaternary ammonium salt modified tea polyphenol-TiO2 composite particles; the ratio of the assembled product, deionized water, and trisodium citrate aqueous solution is 1mg:4mL:5mL; the process conditions for the stirring reaction are: speed 400rpm, time 30min; repeat the operation 4 times; S4: Modified tea polyphenol-TiO2 composite particles, deionized water, and AgNO3 aqueous solution are mixed in a ratio of 1g:80mL:150mL, boiled, and kept for 0.8h, washed, and dried to obtain quaternary ammonium salt modified tea polyphenol-nanosilver composite particles;

[0101] The quaternary ammonium salt-modified tea polyphenol-nanosilver composite particles, methyltetrahydrophthalic anhydride, hexamethyldisiloxane, and polydimethylsiloxane are mixed in a mass ratio of 1:0.03:10:0.04, and stirred evenly to obtain an antibacterial coating;

[0102] (2) Preparation of silver plating solution:

[0103] Dopamine hydrochloride and Tris-HCl buffer were mixed at a mass ratio of 0.10:10 to obtain a dopamine solution;

[0104] S1: polyphenylene sulfide and dopamine solution were mixed in a mass ratio of 1:20, stirred for 1.0 h, and the pH was adjusted to 8.5 to obtain polydopamine-modified polyphenylene sulfide; S2: taurine and deionized water were mixed in a mass ratio of 1:4 to obtain a mixed solution; polydopamine-modified polyphenylene sulfide was mixed with the mixed solution in a mass ratio of 1:3, and under nitrogen atmosphere, the pH was adjusted to 8, stirred for reaction, and dried to obtain sulfonated polyphenylene sulfide;

[0105] Silver nitrate is dissolved in deionized water with stirring, and ammonia water is added until a black flocculent precipitate is formed and then dissolved again to obtain a silver ammonia solution. Glucose, sulfonated polyphenylene sulfide, 5,5-dimethylhydantoin and polyethylene glycol sulfonate are then added and the pH is adjusted to 12 to obtain a silver plating solution.

[0106] The silver plating solution includes the following components by mass: 18 g / L silver nitrate, 25 g / L sulfonated polyphenylene sulfide, 15 g / L glucose, 50 g / L 5,5-dimethylhydantoin, 0.3 g / L polyethylene glycol sulfonate, and 0.13 mL ammonia solution;

[0107] (3) Preparation of stainless steel materials for food-grade straws:

[0108] Take a food grade 316 stainless steel tube, perform plasma treatment, place it in a silver plating solution for chemical silver plating to form a silver plating layer, and then evacuate to 4×10 -3 Pa, argon gas is passed through, plasma silvering treatment is performed to form a silver-infiltrated layer, antibacterial coating is applied, and drying is performed to form an antibacterial coating to obtain a stainless steel material for food-grade straws; plasma treatment uses a mixed gas of argon and oxygen, and the volume ratio of argon to oxygen is 1:4.5; the process conditions of plasma treatment are: mixed gas flow rate 200sccm, processing power 140W, and processing time 2min; the process conditions of silver plating are: plating solution temperature 30℃, electroplating time 20min, current density 3A / dm 2 The process conditions of plasma silvering treatment are: temperature 650℃, voltage 1.2kV, current 4A, time 3h, argon flow rate 30mL / min.

[0109] Example 3: A process for preparing a food-grade stainless steel straw, comprising the following steps:

[0110] (1) Preparation of antibacterial coating:

[0111] S1: Add tea polyphenols into the reactor, pass liquid ammonia, react at low temperature, dry to obtain amino tea polyphenols; mix amino tea polyphenols, deionized water and hexadecyltrimethylammonium bromide at a ratio of 10g:0.1L:40g, heat in a water bath at 60℃ for 1h, let stand for 18h, dry to obtain quaternary ammonium salt modified tea polyphenols; the process conditions of low temperature reaction are: temperature -15℃, pressure 0.1MPa, time 16h; the molar ratio of liquid ammonia to phenolic hydroxyl groups in tea polyphenols is 3:1; S2: Take TiO2, mix it with deionized water, ultrasonically disperse it at 50kHz for 5min, add EDC solution and PAA solution, ultrasonically stir it in an ice bath, wash to obtain modified TiO2; the ratio of TiO2, deionized water, EDC solution and PAA solution is 10mg:50mL:0.05mL:0.25mL; the process conditions of ultrasonic stirring in an ice bath are: frequency 50kHz, time 25min, stirring speed 100rpm; S3: modified TiO2, quaternary ammonium salt modified tea polyphenols, and deionized water are mixed in a ratio of 1mg:3mL:15mL, stirred for reaction, washed to obtain an assembled product, mixed it with deionized water and trisodium citrate aqueous solution, stirred for reaction, washed, and dried to obtain quaternary ammonium salt modified tea polyphenol-TiO2 composite particles; the ratio of the assembled product, deionized water and trisodium citrate aqueous solution is 1mg:5mL:3mL; the process conditions of the stirring reaction are: speed 300rpm, time 20min; repeat the operation 3 times; S4: modified tea polyphenol-TiO2 composite particles, deionized water and AgNO3 aqueous solution are mixed in a ratio of 1g:100mL:100mL, boiled, and kept for 0.5h, washed, and dried to obtain quaternary ammonium salt modified tea polyphenol-nanosilver composite particles;

[0112] The quaternary ammonium salt-modified tea polyphenol-nanosilver composite particles, methyltetrahydrophthalic anhydride, hexamethyldisiloxane, and polydimethylsiloxane are mixed in a mass ratio of 1:0.01:5:0.03, and stirred evenly to obtain an antibacterial coating;

[0113] (2) Preparation of silver plating solution:

[0114] Dopamine hydrochloride and Tris-HCl buffer were mixed at a mass ratio of 0.08:10 to obtain a dopamine solution;

[0115] S1: polyphenylene sulfide and dopamine solution were mixed in a mass ratio of 1:15, stirred for 0.5h, and the pH was adjusted to 8.0 to obtain polydopamine-modified polyphenylene sulfide; S2: taurine and deionized water were mixed in a mass ratio of 1:3 to obtain a mixed solution; polydopamine-modified polyphenylene sulfide was mixed with the mixed solution in a mass ratio of 1:1, and under nitrogen atmosphere, the pH was adjusted to 7, stirred for reaction, and dried to obtain sulfonated polyphenylene sulfide;

[0116] Silver nitrate was dissolved in deionized water with stirring, and ammonia water was added until a black flocculent precipitate was formed and then dissolved again to obtain a silver ammonia solution. Glucose, sulfonated polyphenylene sulfide, 5,5-dimethylhydantoin and polyethylene glycol sulfonate were then added and the pH was adjusted to 11 to obtain a silver plating solution.

[0117] The silver plating solution includes the following components by mass: 15 g / L silver nitrate, 20 g / L sulfonated polyphenylene sulfide, 10 g / L glucose, 40 g / L 5,5-dimethylhydantoin, 0.1 g / L polyethylene glycol sulfonate, and 0.12 mL ammonia water;

[0118] (3) Preparation of stainless steel materials for food-grade straws:

[0119] Take a food grade 316 stainless steel tube, perform plasma treatment, place it in a silver plating solution for chemical silver plating to form a silver plating layer, and then evacuate to 4×10 -3 Pa, argon is passed through, plasma silvering treatment is performed to form a silver-infiltrated layer, antibacterial coating is applied, and drying is performed to form an antibacterial coating to obtain a stainless steel material for food-grade straws; plasma treatment uses a mixed gas of argon and oxygen, and the volume ratio of argon to oxygen is 1:2.5; the process conditions of plasma treatment are: mixed gas flow rate 150sccm, processing power 120W, and processing time 1min; the process conditions of silver plating are: plating solution temperature 20℃, electroplating time 15min, current density 2A / dm 2 The process conditions of plasma silvering treatment are: temperature 600℃, voltage 1.1kV, current 3A, time 2h, argon flow rate 30mL / min.

[0120] Comparative Example 1: Compared with Example 1, sulfonated polyphenylene sulfide was not added to the silver plating solution, and other conditions remained unchanged.

[0121] Comparative Example 2: Compared with Example 1, the quaternary ammonium salt-modified tea polyphenol-nanosilver composite particles were not added to the antibacterial coating, and the other conditions remained unchanged.

[0122] Comparative Example 3: Compared with Example 1, sulfonated polyphenylene sulfide was not added to the silver plating solution, and quaternary ammonium salt-modified tea polyphenol-nanosilver composite particles were not added to the antibacterial coating, while other conditions remained unchanged.

[0123] Experiment: The food-grade stainless steel materials for straws obtained in the examples and comparative examples were tested for their antibacterial properties and wear resistance.

[0124] Antibacterial performance test: Escherichia coli, Candida albicans, Salmonella, and Staphylococcus aureus were used as experimental bacteria. The bacteria were inoculated on food-grade stainless steel pipettes using the agar plate method. The sterilization rate after 24 hours was calculated and recorded.

[0125] Wear resistance test: The antibacterial coating on the surface of stainless steel used for food-grade straws was tested using an eraser wear tester. The rotation parameter of the wear tester was set to 80 rpm, the eraser load was selected to be 500 g, one round trip friction was set as one time, and the number of frictions was set to 1000 times. The quality before and after wear was recorded.

[0126] Table 1 Test results of antibacterial properties of stainless steel materials

[0127]

[0128] Table 2 Test results of wear resistance of stainless steel materials

[0129]

[0130] According to the test results in the above table, compared with Example 1, in Comparative Example 1, no sulfonated polyphenylene sulfide was added to the silver plating solution, and the wear quality of the stainless steel material increased. This shows that the present invention introduces sulfonated polyphenylene sulfide into the silver plating solution and utilizes the wear resistance of polyphenylene sulfide itself to reduce the wear on the surface of the stainless steel material and extend the service life.

[0131] Compared with Example 1, in Comparative Example 2, no quaternary ammonium salt-modified tea polyphenol-nanosilver composite particles were added to the antibacterial coating. The antibacterial property of the stainless steel material decreased significantly, and the wear quality was also improved. This shows that the synergistic antibacterial effect between the quaternary ammonium salt, tea polyphenol and nanosilver can make the stainless steel material have better antibacterial property, and TiO2 also has good weather resistance, which can reduce wear to a certain extent.

[0132] Compared with Example 1, Comparative Example 3 does not add sulfonated polyphenylene sulfide to the silver plating solution, and does not add quaternary ammonium salt-modified tea polyphenol-nanosilver composite particles to the antibacterial coating. This shows that the setting of the materials and process conditions used in the present invention can promote the improvement of the antibacterial and wear resistance of the prepared food-grade stainless steel material.

[0133] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations that come within the meaning and range of equivalents of the claims be embraced therein.

Claims

1. A process for preparing stainless steel material for food-grade straws, characterized by: The following steps are involved: Take the stainless steel tube, place it in the silver plating solution for chemical silver plating to form a silver plating layer, and then evacuate to 4×10 -3 Pa, plasma silvering treatment is performed to form a silver-infiltrated layer to obtain a stainless steel material for food-grade straws; The silver plating solution comprises the following components by mass: 15 g / L to 20 g / L silver nitrate, 20 g / L to 30 g / L sulfonated polyphenylene sulfide, 10 g / L to 20 g / L glucose, 40 g / L to 60 g / L 5,5-dimethylhydantoin, 0.1 g / L to 0.5 g / L polyethylene glycol sulfonate, and 0.12 mL to 0.14 mL ammonia water; The solvent of the silver plating solution is deionized water; The surface of the silver-infiltrated layer is provided with an antibacterial coating, which is formed by coating and drying an antibacterial coating; The antibacterial coating is prepared by the following process: The quaternary ammonium salt-modified tea polyphenol-nanosilver composite particles, a curing agent, a solvent, and a leveling agent are mixed and stirred evenly to obtain an antibacterial coating; The quaternary ammonium salt modified tea polyphenol-nanosilver composite particles are prepared by the following process: S1: adding tea polyphenols to a reactor, passing liquid ammonia, reacting at low temperature, and drying to obtain amino tea polyphenols; mixing amino tea polyphenols, deionized water, and long-chain quaternary ammonium salt, heating in a water bath for reaction, standing for 18 h to 22 h, and drying to obtain quaternary ammonium salt-modified tea polyphenols; S2: Take TiO2, mix it with deionized water, disperse it by ultrasonic, add EDC solution and PAA solution, stir it by ultrasonic in an ice bath, and wash it to obtain modified TiO2; S3: Mixing the modified TiO2, quaternary ammonium salt-modified tea polyphenols, and deionized water, stirring and reacting, washing, and obtaining an assembled product, mixing the assembled product with deionized water and a 0.5 mg / mL trisodium citrate aqueous solution, stirring and reacting, washing, and drying to obtain quaternary ammonium salt-modified tea polyphenol-TiO2 composite particles; S4: mixing the modified tea polyphenol-TiO2 composite particles, deionized water and AgNO3 aqueous solution, boiling, and maintaining for 0.5h~1h, washing, and drying to obtain quaternary ammonium salt modified tea polyphenol-nanosilver composite particles; The sulfonated polyphenylene sulfide is prepared by the following process: S1: mixing polyphenylene sulfide and dopamine solution, stirring for 0.5 h to 1.5 h, and adjusting the pH to 8.0 to 9.0 to obtain polydopamine-modified polyphenylene sulfide; S2: taurine is mixed with deionized water to obtain a mixed solution; polydopamine-modified polyphenylene sulfide is mixed with the mixed solution, and under the protection of a nitrogen atmosphere, the pH is adjusted to 7-9, the reaction is stirred, and the mixture is dried to obtain sulfonated polyphenylene sulfide.

2. The process for preparing a food-grade stainless steel material for straws according to claim 1, characterized in that: The gas used in the plasma silvering treatment is argon; The process conditions of the plasma silvering treatment are: temperature 600° C. to 700° C., voltage 1.1 kV to 1.3 kV, current 3 A to 5 A, time 2 h to 4 h, and argon flow rate 30 mL / min to 50 mL / min.

3. The process for preparing a food-grade stainless steel material for straws according to claim 1, characterized in that: The stainless steel tube is subjected to plasma treatment using a mixed gas of argon and oxygen before chemical silver plating; the volume ratio of argon to oxygen is 1:(2.5-6.5); The process conditions of the plasma treatment are: mixed gas flow rate 150 sccm~250 sccm, treatment power 120 W~160 W, and treatment time 1 min~3 min.

4. The process for preparing a food-grade stainless steel straw according to claim 1, wherein: The mass ratio of the quaternary ammonium salt modified tea polyphenol-nanosilver composite particles, the curing agent, the solvent, and the leveling agent is 1: (0.01-0.05): (5-15): (0.03-0.05).

5. The process for preparing a food-grade stainless steel straw according to claim 1, characterized in that: In S1, the molar ratio of liquid ammonia to phenolic hydroxyl groups in tea polyphenols is (3-5):1; In S1, the ratio of amino tea polyphenols, deionized water and long-chain quaternary ammonium salt is 10g: (0.05~0.1)L: (40~60)g.

6. The process for preparing a food-grade stainless steel material for straws according to claim 1, characterized in that: In S2, the ratio of TiO2, deionized water, EDC and PMMA is 10 mg: (10-50) mL: (0.05-0.1) mL: (0.25-0.45) mL.

7. A food-grade stainless steel straw, characterized by: Obtained according to the preparation process according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Bacteriostatic deodorant super absorbent resin and absorbent products of super absorbent resin

    CN107501462A

  • Antibacterial stainless steel band with high surface quality and preparation method thereof

    CN119332318A